Implementation of Customer Relationship Management System to Maintain Service Quality for Customer - Sri Rahayu; Pandu Adi Cakranegara; Tienni Mariana Simanjorang; Sy Nurul Syobah; Arifin (Institute of Computer Science (IOCS), 2022)
Competition in the business world is accompanied by the development of the world of information and communication technology. Technological advances promote digital business trends that require every goods or service company to be able to present their merchandise online, either on business websites or on existing e-commerce platforms, and support digital transactions. between seller and buyer. The ease of transaction for customers is a crucial aspect of the service and process of buying and selling. In an effort to thrive in the competitive business environment, it is a struggle for businesspeople to deliver services that suit the needs of their clients since customers are becoming more discerning and their comfort standards are rising. Improving service to customers is the primary focus of every business in order to consider ways and business processes to maintain customer loyalty; therefore, the objective of this research is to design and build a computerized system to make it easier for businesses to manage the transaction process and to determine the superior features of the system in relation to improving service to customers. By installing a Customer Relationship Management (CRM) system, you may acquire new clients and keep the loyalty of existing ones. The Customer Relationship Management (CRM) system is established to aid administrators in the management of transactional operations, product management, flagship initiatives, and customer promotions. as envisioned and valid for all primary system menu functions, so that it can be developed throughout the implementation phase.